Managing Conflicts in Joint Venture Projects - Abd-Karim, S. B.; Abg Marani, D.A.; Mohd Danuri, M. S.; Mohamed, O. (International Journal of Property Sciences (E-ISSN: 2229-8568), 2014)
A joint venture (JV) involves two or more businesses pooling their resources and expertise to achieve a particular goal, where the risks and rewards are shared. JV has become popular because of their importance as a strategic alternative in global competition. The number of JV has increased over the past two decades due to intensified technology, competitive challenges and market globalisation but it is important to understand what causes some JV to fail and others to succeed. Conflict is the main reason that causes some JV to fail. It may create problems in future planning and have negative effects on the financial performance of the firm that would affect JV survival. Hence, the study concentrates on the JV relationship between partners in the Malaysian construction industry in order to identify the effective ways in managing conflicts. A total of 100 questionnaires were distributed to the selected respondents and the finding shows that all of the respondents experienced conflict in the JV and the conflict management team seems to be inexistent to manage the conflict. Some recommendations in managing conflict are dictated by discussing the problem such as open talk, self-patience, endurance and being decisive as well as educating all the staffs in handling conflict.